Reduction process of low grade iron ore using palm kernel shell and empty fruit bunch / by Rusila Zamani Binti Jusoh @ Abd Rashid - Rusila Zamani binti Jusoh @ Abd Rashid (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
The depletion of high grade iron ore sources, the rapid change in coal prices, and the environmental pollution generated from using coke pose serious problems and demand sustainable solutions for the iron and steel industries. Malaysia has abundant deposits of low grade iron and easily available biomass agro-residues from the palm oil industry. Effective use of the local iron ore and the biomass residues as material and energy resources, respectively, in the iron making process, is an interesting economic prospect, since Malaysia imports iron ore to supply its domestic iron consumption. The aim of this work is to study the reducibility and mechanisms of the composite pellet using palm kernel shell and empty fruit bunch at different temperatures and biomass contents, as well as to analyze the kinetics of the composite pellet reduction process and to evaluate the magnetic properties of the composite pellet. Chini iron ore sample was subjected to thermal and X-ray diffraction (XRD) analysis. The iron ore with palm kernel shell and/or empty fruit bunch were mixed with minute amount of water at several formulations of iron ore to biomass and then fabricated into composite pellets with average spherical diameter of 10-12 mm. The composite pellet was subjected to a reduction test for 30 minutes using an electric tube furnace up to 900ºC. The reduction degree increases with increasing temperature and the biomass content up to 40 wt. %. XRD analysis revealed that the low grade iron ore mainly contained iron oxide hydrate and was converted into simple hematite after heating. It then became magnetite, wustite, and metallic iron after the reduction process. The Fe content in the low grade iron ore increased almost 11-12% when 40 wt. % of biomass was used. The magnetic saturation of the iron ore increased up to 47.1 emu/g and its magnetic susceptibility was enhanced to 44.6 x 10-3 emu/g, which is a 40 fold increase from the original iron ore when heated with 40 wt. % empty fruit bunch. Kinetics analysis revealed that the reaction in the composite pellet was controlled by a chemical reaction with activation energy of 115.32 kJ/mol. Thus, the utilization of biomass as an energy source in the reduction of low grade iron ore is an attractive method for reducing CO2 emission and promoting green technology.